2004
DOI: 10.1016/j.cub.2004.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Heparan Sulfate Proteoglycan Syndecan Promotes Axonal and Myotube Guidance by Slit/Robo Signaling

Abstract: Slit, the ligand for the Roundabout (Robo) receptors, is secreted from midline cells of the Drosophila central nervous system (CNS). It acts as a short-range repellent that controls midline crossing of axons and allows growth cones to select specific pathways along each side of the midline. In addition, Slit directs the migration of muscle precursors and ventral branches of the tracheal system, showing that it provides long-range activity beyond the limit of the developing CNS. Biochemical studies suggest that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
116
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(123 citation statements)
references
References 24 publications
7
116
0
Order By: Relevance
“…These experiments did not reveal which HSPGs are critical for Slit-Robo signalling, however. A first clue came from the observation that the expression patterns of Robo and the HSPG syndecan overlap in the Drosophila nervous system [22,23]. Genetic experiments in Drosophila and C. elegans indeed demonstrated that syndecan has to be present on the same axon as Robo for Slit-Robo signalling to occur normally [22][23][24].…”
Section: Slit-hs Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…These experiments did not reveal which HSPGs are critical for Slit-Robo signalling, however. A first clue came from the observation that the expression patterns of Robo and the HSPG syndecan overlap in the Drosophila nervous system [22,23]. Genetic experiments in Drosophila and C. elegans indeed demonstrated that syndecan has to be present on the same axon as Robo for Slit-Robo signalling to occur normally [22][23][24].…”
Section: Slit-hs Interactionsmentioning
confidence: 98%
“…To add further complexity, Robos also appear to have a Slit-independent function in homophilic cell adhesion [21]. Finally, the HSPG [HS (heparan sulphate) proteoglycan] syndecan was recently identified as a coreceptor for Slit [22][23][24]. While the importance of Slit-Robo signalling for many biological processes is well established, our understanding of the molecular mechanisms involved is limited.…”
Section: Introductionmentioning
confidence: 96%
“…Each family member has a unique extracellular domain sequence, but all This article was published online ahead of print in MBC in Press (http://www.molbiolcell.org/cgi/doi/10.1091/mbc.E04 -10 -0907) on June 1, 2005. contain sites for addition of glycosaminoglycan (GAG) chains proximal to the amino-terminus (reviewed by Rapraeger and Ott, 1998;Bernfield et al, 1999). Many functions of syndecans result from their activities as coreceptors through the binding of growth factors to the GAG chains (for example, Johnson et al, 2004;Steigemann et al, 2004). The transmembrane domains are highly conserved and the short cytoplasmic domains contain two conserved regions, C1 and C2, that have the same sequence in all syndecan family members.…”
Section: Introductionmentioning
confidence: 99%
“…Of note is that all Robo receptors except for Robo4 contain the Ig domain, which binds to Slit2 [33]. Thus, it is possible that a co-receptor, such as Robo1, syndecans [36], or heparan sulfate [37], is required for Slit2/Robo4 interaction. A recent genetic study has clearly shown that Slit2 is involved in Robo4-mediated downregulation of VEGF angiogenesis in breast [38].…”
Section: Discussionmentioning
confidence: 96%